Students’ Responses Toward Teachers’ Translanguaging Practice at an Islamic Public Senior High School - Brillianti, Sabrina; Madjid, Hilda Izzati; Rofiq, Ainur (ICONELT, 2024)
Translanguaging, a language teaching approach which is now widely used, has been recognized as a language teaching approach that has a myriad of benefits. However, as the research and positive elaborations of this approach continue to grow, there are also many speculations and negative views from some educators about the use of translanguaging. The existence of these two sides invites translanguaging into a circle of pros and cons. The establishment of an islamic senior high school that applies translanguaging in three languages might lead to the students’ responses towards teachers’ translanguaging practices used in the classroom. Using a qualitative case study, the data from an open-ended questionnaire responded by 71 students from two classes were analyzed. As a result, most students gave more positive responses to the teacher's translanguaging. They believed translanguaging as a tool to make them become more familiar with English since not all of them are good at L2 acquisition. Although many of them responded positively, a small number of students felt that the use of another language in English learning was not good for the development of their skills in the target language. They thought that English should be used more frequently if they wanted better results in the learning process.